Online Food Ordering System in Triple L Café by Scanning Quick Response (QR) Code - Wong, Pik Keen; Kamaludin, Hazalila (Applied Information Technology And Computer Science, 2024)
The Android-based Online Food Ordering System was developed for Triple L Café, which currently uses a manual food ordering system. The manual system results in errors and waste of cost and time. The system aims to increase the efficiency of daily business by providing a QR code for the customer to scan and place their order online. The methodology used to develop the system is the Prototype Model. Flutter is the system development platform, and Dart is the primary language for system development. Firebase acts as data storage. Stripe powers online payment processing in the developed system. QR is provided for customers to scan and access the system. The developed system has a user-friendly interface with full functionality. Through the User Acceptance Test (UAT) result, the administrator was very satisfied with 7 out of 8 features, while 93.33% of customer respondents agreed that the system is easy to use.